2005
DOI: 10.1079/asc41150209
|View full text |Cite
|
Sign up to set email alerts
|

The effect of varying levels of mineral and iodine supplementation to ewes during late pregnancy on serum immunoglobulin G concentrations in their progeny

Abstract: Three experiments were carried out to evaluate the effects of varying levels of mineral and iodine supplements when offered to ewes in late pregnancy on lamb serum immunoglobulin G (IgG) concentrations. In experiment 1, 44 individually housed ewes were allocated to one of four treatments (no. = 11) and offered a basal diet of grass silage ad libitum which was supplemented with 500 g/day of a concentrate (190 g/kg of crude protein (CP)), in addition to mineral/vitamin fortification at the rate of 0 g (C), 17.3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
1
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 19 publications
4
31
1
1
Order By: Relevance
“…The cobalt requirements of sheep are 0.07 mg/kg DM per day (Agricultural Research Council (ARC), 1980) and the concentrations fed in the current study were higher than the requirements of 0.13 mg per ewe per day as outlined by Boland et al (2004). The levels of mineral supplementation offered in this study did not reach the current quoted toxicity levels (ARC, 1980) but the findings of this study and recent work (Boland et al, 2005a(Boland et al, , 2005b(Boland et al, and 2006 show that high levels of iodine inclusion can have negative effects on animal performance even at rates below the quoted toxicity level. Based on these findings, the indications are that the toxicity level for iodine in the diet of the pregnant ewe should be lowered to 20 mg per ewe per day, equivalent to 40% of its current level.…”
Section: Discussioncontrasting
confidence: 71%
See 4 more Smart Citations
“…The cobalt requirements of sheep are 0.07 mg/kg DM per day (Agricultural Research Council (ARC), 1980) and the concentrations fed in the current study were higher than the requirements of 0.13 mg per ewe per day as outlined by Boland et al (2004). The levels of mineral supplementation offered in this study did not reach the current quoted toxicity levels (ARC, 1980) but the findings of this study and recent work (Boland et al, 2005a(Boland et al, , 2005b(Boland et al, and 2006 show that high levels of iodine inclusion can have negative effects on animal performance even at rates below the quoted toxicity level. Based on these findings, the indications are that the toxicity level for iodine in the diet of the pregnant ewe should be lowered to 20 mg per ewe per day, equivalent to 40% of its current level.…”
Section: Discussioncontrasting
confidence: 71%
“…Recent results have shown that although lambs may appear to receive an adequate supply of colostrum containing sufficient levels of IgG, their serum IgG concentrations can be low, indicating a poor IgG absorption efficiency which leaves the lambs extremely susceptible to infections Crosby et al, 2004;Guinan et al, 2005). A negative linear relationship has been demonstrated between iodine level and serum IgG concentration (Boland et al, 2005b) and these new findings suggest that there may also be a similar relationship between the period of supplementation and serum IgG concentration. Although the serum IgG concentration at 24 h in the I-1 lambs was significantly lower than in the C lambs, it was intermediate between the C and I-3 lambs, indicating that a supplementation period of more than 1 week is required to see the complete negative effects of high levels of iodine supplementation on lamb serum IgG concentration.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations